Preliminary Results of a New Illuminated Radiofrequency Ablation Catheter for the Treatment of Great Saphenous Vein Reflux Disease - Beyaz, Metin Onur; Oztas, Didem Melis; Ulukan, Mustafa Ozer; Arslan, Hasan Murat; Unal, Orcun; Ugurlucan, Murat (Surgical innovation, 2022)
: In the current study, we present single surgeon experience of a new radiofrequency ablation system, the catheter, and the device. : The new system, which comprises a generator and an intervally illuminated radiofrequency ablation catheter, was used for the treatment of 272 consecutive patients with chronic venous insufficiency of the great saphenous vein between November 2017 and October 2018. Mean age of the patients was 53.40 ± 11.91 years. Mean saphenous vein diameter was 8.51 ± 2.45 mm. Bilateral great saphenous vein reflux disease was present in 19% (51 cases) of the patients. At the end of the procedure, the closure of the great saphenous vein was confirmed with Doppler ultrasonography. : Procedures could be successfully performed in all, except 1 obese (BMI> 30 kg/m ) male patient. At the 3rd month, outpatient clinic follow-up control Doppler USG revealed successful ablation of the treated great saphenous vein in 260 patients (96%), whereas in 12 cases (4%), there was continuing reflux. The diameters of the saphenous veins in these patients ranged between 6.9 mm and 19.5 (mean: 10.68 ± 3.41) mm. Ten patients could be treated successfully with ablation with the same device controlled both at the interventional section as well as on the 3rd month outpatient clinic follow-up. The remaining patients underwent high ligation of the great saphenous vein. Paresthesia occurred in 1 patient and had been permanent. Hematoma occurred in a male patient and resolved spontaneously. : Preliminary results of our new radiofrequency ablation device with illumination guidance for the treatment of great saphenous vein reflux disease indicated successful results with enhanced physician utilization, comfort, and reliability.